Levels of orientation bias differ across digital content categories: Implications for visual perception. (April 2023) - Duggan, Nicholas; Gerhardstein, Peter
With the continued growth of digital device use, a greater portion of the visual world experienced daily by many people has shifted towards digital environments. The "oblique effect" denotes a bias for horizontal and vertical (canonical) contours over oblique contours, which is derived from a disproportionate exposure to canonical content. Carpentered environments have been shown to possess proportionally more canonical than oblique contours, leading to perceptual bias in those who live in "built" environments. Likewise, there is potential for orientation sensitivity to be shaped by frequent exposure to digital content. The potential influence of digital content on the oblique effect was investigated by measuring the degree of orientation anisotropy from a range of digital scenes using Fourier analysis. Content from popular cartoons, video games, and social communication websites was compared to real-life nature, suburban, and urban scenes. Findings suggest that digital content varies widely in orientation anisotropy, but pixelated video games and social communication websites were found to exhibit a degree of orientation anisotropy substantially exceeding that observed in all measured categories of real-world environments. Therefore, the potential may exist for digital content to induce an even greater shift in orientation bias than has been observed in previous research. This potential, and implications of such a shift, is discussed.